A new Mexican species of the genus Onthophagus Latreille, 1802 (Coleoptera: Scarabaeidae). (2nd January 2023) - Moctezuma, Victor; Sánchez-Huerta, José Luis; Hernández, Benjamín
ABSTRACT: Onthophagus manantlanensis Sánchez-Huerta, Moctezuma & Hernández, a new species is described from Jalisco, Mexico. Onthophagus manantlanensis is similar in morphology to O. villanuevai . Consequently, the new species is preliminarily included within the O. clypeatus species group. The new O. manantlanensis, along with O. villanuevai, O. nasutus Guérin-Méneville, 1855, O. atriglabrus Howden & Gill, 1987 and O. nasicornis Harold, 1869 might be related species within the O. clypeatus species group. To date, the New World Onthophagus Latreille, 1802 includes about 190 described species, 121 of them are known from Mexico, of which 34 species form the O. clypeatus species group. A distribution map and images of O. manantlanensis and O. villanuevai are provided. http://www.zoobank.org/urn:lsid:zoobank.org:pub:D4A093F4-B59D-470B-99FC-66452524C919